The radiation sterilization technique applied to the powder of Nelumbo nucifera - SHEN Wei-qiao (浙江大学学报. 农业与生命科学版, 2000)
Using 60Coy-ray irradiation sterilizat technique for ion powder of Nelumbo nucifera was studied. The appropriate irradiation dose for sterilization was 6 kGy. The results demonstrated that the microorganism in the products can be sterilized efficiently with γ-ray irradiation. There was no significant differences in the quality of the product before and after γ-radiation, however, the viscosity of starch decreased with the increase of the irradiation dose.